The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1123/tsp.25.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to the Onset of Eating Disorders Reported by Female Collegiate Athletes

Abstract: The purpose of this study was to identify factors related to the onset of eating disorders in female athletes. Participants were 17 collegiate female athletes (mean age of 20.7) who experienced eating disorders. Participants were interviewed individually and responses were coded thematically. Results revealed internal and external factors related to the onset of eating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Especially in weight-sensitive sports, weight loss of one athlete may influence the dieting behaviour of the others. In the desire to be “better than her/him”, athletes can be influenced by the thought that “If she/he is losing more weight, then I need to lose some too!” or the perception that they are “bigger” than their teammates [ 55 ]. Furthermore, teammates can share more drastic methods to lose weight [ 56 ].…”
Section: Reason For Lea and Prevalence In Different Sports Across Sexmentioning
confidence: 99%
“…Especially in weight-sensitive sports, weight loss of one athlete may influence the dieting behaviour of the others. In the desire to be “better than her/him”, athletes can be influenced by the thought that “If she/he is losing more weight, then I need to lose some too!” or the perception that they are “bigger” than their teammates [ 55 ]. Furthermore, teammates can share more drastic methods to lose weight [ 56 ].…”
Section: Reason For Lea and Prevalence In Different Sports Across Sexmentioning
confidence: 99%
“…Modelled behaviours are those adopted behaviours that have been reinforced as the norm in a group and those modelled behaviours pertaining to eating psychopathology have been shown to increase disordered eating symptomology [53,54]. The mediator that is termed modelled behaviour by peers and family is one that much of the literature has overlooked, and research has yet to operationalise or validate a measurement tool for this potential risk factor.…”
Section: Modelled Behavioursmentioning
confidence: 99%
“…Reliability analysis for the current study found the alpha to be .61. In the current study, questions were designed based on the qualitative results that had previously discussed the harmful role that modelled behaviours of teammates can have in the development of eating disorders [54].…”
Section: Modelled Behavioursmentioning
confidence: 99%
“…Coaches therefore often appear to be ill-informed about the subject matter without being aware of it. 20 They need further training about eating disorders and athlete education so knowledge can be passed on in an open and supportive environment. Encouraging an open dialogue may allow a stronger bond to form between coaches and their athletes that might facilitate earlier interventions for maladaptive behaviors.…”
Section: How Do Female Collegiate Athletes View Their Education Aboutmentioning
confidence: 99%